The good wife. The sixth season [videorecording (DVD)] - Margulies, Julianna, 1966-; Baranski, Christine; Panjabi, Archie; Cumming, Alan, 1965-; Noth, Chris, 1954- ([Publisher not identified], 2015)
Alicia Florrick stood by her husband on his tumultuous path to the governor's office, but now she's entering the world of politics on her own terms by running for state's attorney. As Election Day approaches, Alicia must balance the demands of her firm and campaign as she supports her partner Cary during shocking developments that could end his career; and life as he knows it.